Disorder effects on the static scattering function of star branched polymers - Blavatska, V.; von Ferber, C.; Holovatch, Yu. (Condensed Matter Physics, 2012)
We present an analysis of the impact of structural disorder on the static scattering function of f-armed star branched polymers in d dimensions. To this end, we consider the model of a star polymer immersed in a good solvent in the presence of structural defects, correlated at large distances r according to a power law ~r-a. In particular, we are interested in the ratio g(f) of the radii of gyration of star and linear polymers of the same molecular weight, which is a universal experimentally measurable quantity. We apply a direct polymer renormalization approach and evaluate the results within the double ϵ = 4 - d, δ = 4 - a-expansion. We find an increase of g(f) with an increasing δ. Therefore, an increase of disorder correlations leads to an increase of the size measure of a star relative to linear polymers of the same molecular weight. Представлено аналiз впливу структурного безладу на статичну функцiю розсiяння f -гiлкового зiркового полiмера у d-вимiрному просторi. Розглянуто модель зiркового полiмера у хорошому розчиннику в при-сутностi структурних дефектiв, скорельованих на великих вiддалях r згiдно степеневого закону ∼ r −a. Зокрема, ми цiкавимось вiдношенням g(f ) iнтенсивностей розсiяння зiркового та лiнiйного полiмерiв однакової молекулярної маси, що є унiверсальною, експериментально спостережуваною величиною. Ми застосовуємо метод прямого полiмерного перенормування i використовуємо подвiйний ε = 4 − d, δ = 4−a-розклад. Знайдено зростання величини g(f ) iз зростанням параметра δ. Таким чином, зростання кореляцiй безладу приводить до зменшення вiдмiнностi мiж розмiром зiркових та лiнiйних полiмерiв iз однаковою молекулярною вагою.